Multiple Signals Regulate GAL Transcription in Yeast - Rohde, John R. (American Society for Microbiology, 2000)
Gal4p activates transcription of the Saccharomyces GAL genes in response to galactose and is phosphorylated during interaction with the RNA polymerase II (Pol II) holoenzyme. One phosphorylation at S699 is necessary for full GAL induction and is mediated by Srb10p/CDK8 of the RNA Pol II holoenzyme mediator subcomplex. Gal4p S699 phosphorylation is necessary for sensitive response to inducer, and its requirement for GAL induction can be abrogated by high concentrations of galactose in strains expressing wild-type GAL2 and GAL3. Gal4p S699 phosphorylation occurs independently of Gal3p and is responsible for the long-term adaptation response observed in gal3 yeast. SRB10 and GAL3 are shown to represent parallel mechanisms for GAL gene induction. These results demonstrate that Gal4p activity is controlled by two independent signals: one that acts through Gal3p-galactose and a second that is mediated by the holoenzyme-associated cyclin-dependent kinase Srb10p. Since Srb10p is regulated independently of galactose, our results suggest a function for CDK8 in coordinating responses to specific inducers with the environment through the phosphorylation of gene-specific activators.